2011
DOI: 10.1002/micr.20964
|View full text |Cite
|
Sign up to set email alerts
|

The radio‐radial nerve transfer for elbow extension restoration in C5 to C7 nerve root injury

Abstract: Extension of the elbow is required to oppose gravity; however, activation of the triceps brachii is frequently underestimated during the surgical planning for brachial plexus injuries. This report aims to describe a novel technique of distal nerve transfer designed for elbow extension reconstruction in patients sustaining a C5-C7 nerve root injury. We report a patient sustaining a brachial plexus injury with triceps palsy and preserved finger extension motion; after careful intraneural dissection of the radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Oberlin et al performed a transfer of a redundant motor fascicle of the ulnar nerve to the biceps motor branch with successful elbow flexion restoration. After him, many other nerve transfers were developed using the same principle: use of expendable fascicles from healthy nerves to reconstruct priority functions of the upper extremity in brachial plexus and other peripheral nerve injuries …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oberlin et al performed a transfer of a redundant motor fascicle of the ulnar nerve to the biceps motor branch with successful elbow flexion restoration. After him, many other nerve transfers were developed using the same principle: use of expendable fascicles from healthy nerves to reconstruct priority functions of the upper extremity in brachial plexus and other peripheral nerve injuries …”
Section: Discussionmentioning
confidence: 99%
“…After him, many other nerve transfers were developed using the same principle: use of expendable fascicles from healthy nerves to reconstruct priority functions of the upper extremity in brachial plexus and other peripheral nerve injuries. [13][14][15][16][17] Currently, the ulnar nerve fascicle transfer is by far more frequently used than the median nerve fascicle transfer for biceps reinervation, even though some authors have demonstrated that the median nerve fascicle transfer is technically easier to perform and yields similar good results. 18,19 One of the reasons for that may be the concerns about the integrity of the motor component of the median nerve in C5-C7 injuries, which could lead to suboptimal results of biceps recovery.…”
Section: Discussionmentioning
confidence: 99%
“…One variation in the original technique, which increases the number of axons reaching the agonist target muscles (e.g., double transfers from ulnar to biceps and median to brachialis nerves) has generated even better results; between 95% and 99% of patients experience a good result. Other distal nerve transfers based on this concept (e.g., triceps branch-axillary nerve transfer [so-called Somsak procedure] 33,62 and wrist and finger extension branch-triceps branch transfer 18 ) have also been associated with very high success rates.…”
Section: Plasticity In Distal Nerve Transfers In Relation To Adjacencmentioning
confidence: 99%
“…The epineurium of the radial nerve was longitudinally incised, and a careful intra-neural dissection was carried out to identify the function of each fascicle. With low-voltage electrical stimulation (0.2 mV), a redundant fascicle innervating the extensor digitorum muscle was identified, divided, and sutured to the branch of the lateral head of the triceps with one 10-0 microsuture and fibrin glue (Flores, 2012b).…”
Section: Methodsmentioning
confidence: 99%